Pengaruh Celebrity Worship dan Kesepian terhadap Kecenderungan Adiksi Internet pada Remaja Penggemar K-Pop - Okmy Intan Cahyani; Alif Muhammad Zakaria; Faatihatul Ghaybiyyah (Islamic Extension Guidance Study Program (BPI) of the Faculty of Da'wah and Communication, 2022)
Abstract: Korean music, also known as K-Pop, is currently being loved by teenagers. This study aims to determine the effect of celebrity worship and loneliness together and partially on the tendency of internet addiction in adolescent K-Pop fans. The sample in this study was determined through a purposive sampling technique with the characteristics of young K-pop fans, the number of samples that were obtained was 210 people. Data collection techniques used three types of scales, namely, the celebrity worship scale consisting of 21 items (α = 0.897), the loneliness scale consisting of 11 items (α = 0.920), and the internet addiction tendency scale consisting of 27 items (α = 0.903). The data analysis technique is multiple linear analysis. The results showed that there was a significant positive effect between celebrity worship and loneliness with internet addiction tendencies in K-Pop fans, there was a positive influence between celebrity worship and internet addiction tendencies, and there was a positive relationship between loneliness and internet addiction tendencies.Abstrak: Musik Korea atau yang dikenal K-Pop saat ini tengah disukai oleh kalangan remaja. Penelitian ini bertujuan untuk mengetahui pengaruh celebrity worship dan kesepian secara bersama–sama dan parsial terhadap kecenderungan adiksi internet pada remaja penggemar K-Pop.Sampel pada penelitian ini ditentukan melaui teknik purposive sampling dengan karakteristik remaja penggemar K-pop, jumlah sampel yang berhasil didapat sebanyak 210 orang. Teknik pengumpulan data menggunakan tiga jenis skala yaitu, skala celebrity worship terdiri 21 butir (α = 0,897), skala kesepian yang terdiri 11 butir (α = 0,920), dan skala kecenderungan adiksi internet yang terdiri 27 butir (α = 0,903). Adapun teknik analisis data adalah analisis linier berganda. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif signifikan antara celebrity worship dan kesepian dengan kecenderungan adiksi internet pada remaja penggemar K-Pop, terdapat pengaruh positif antara celebrity worship terhadap kecenderungan adiksi internet, dan terdapat hubungan positif antara kesepian terhadap kecenderungan adiksi internet.